Characterization of In Vivo Retinal Lesions of Diabetic Retinopathy Using Adaptive Optics Scanning Laser Ophthalmoscopy - Sonja G. Karst; Jan Lammer; Salma H. Radwan; Hanna Kwak; Paolo S. Silva; Stephen A. Burns; Lloyd Paul Aiello; Jennifer K. Sun (International Journal of Endocrinology)
Purpose. To characterize hallmark diabetic retinopathy (DR) lesions utilizing adaptive optics scanning laser ophthalmoscopy (AOSLO) and to compare AOSLO findings with those on standard imaging techniques. Methods. Cross-sectional study including 35 eyes of 34 study participants. AOSLO confocal and multiply scattered light (MSL) imaging were performed in eyes with DR. Color fundus photographs (CF), infrared images of the macula (Spectralis, Heidelberg), and Spectralis spectral domain optical coherence tomography SDOCT B-scans of each lesion were obtained and registered to corresponding AOSLO images. Main Outcome Measures. Individual lesion characterization by AOSLO imaging. AOSLO appearance was compared with CF and SDOCT imaging. Results. Characterized lesions encompassed 52 microaneurysms (MA), 20 intraretinal microvascular abnormalities (IRMA), 7 neovascularization (NV), 11 hard exudates (HE), 5 dot/blot hemorrhages (HEM), 4 cotton wool spots (CWS), and 14 intraretinal cysts. AOSLO allowed assessment of perfusion in vascular lesions and enabled the identification of vascular lesions that could not be visualized on CF or SDOCT. Conclusions. AOSLO imaging provides detailed, noninvasive in vivo visualization of DR lesions enhancing the assessment of morphological characteristics. These unique AOSLO attributes may enable new insights into the pathological changes of DR in response to disease onset, development, regression, and response to therapy.